The Rising Trend of Divorce Cases: Social and Psychological Implications in Modern Society - Wafi, Abdul; Jannah, Shofiatul (Jurnal Ius Constituendum, 2024)
The purpose of this study is to explore the social and psychological impacts of the high divorce rate in Malang caused by economic problems. Because the high divorce rate in Malang City shows a complex problem in marriage relationships, The main factor that causes this high divorce rate is the continuous disputes between couples. This dispute, in the end, can be traced back to the economic problems experienced by couples who file for divorce. With this problem, it is important to do further research to find solutions to problems that occur in society. The research method used was qualitative analysis by conducting in-depth interviews with judges who directly handled divorce cases at the Malang City religious court. The results showed that the high divorce rate in Malang City can be attributed to factors such as prolonged disputes between couples as well as increased economic pressure. Constant bickering can damage the emotional bond and communication between couples, triggering the decision to end the marriage through legal proceedings. The social implications include family breakups that can impact children and close relatives, while the psychological impact includes stress, depression, and emotional instability for all parties involved. A deep understanding of these impacts is important for developing prevention and social support efforts that can help reduce divorce rates and provide assistance to those involved in divorce proceedings.